Justice and the fundamental right to the environment (2018)
The objective of the text is to analyze environmental justice and the fundamental right to the environment as a way of guaranteeing and realizing the existential minimum in the light of John Rawls’ conception of justice. From an analytical approach, the thesis is developed that the fundamental right to the environment isadded to the group of fundamental rights, arguing that the ecological existential minimum can be sustained as a corollary of the dignity of the human person. We start from the Rawlsian theory of justice to base the protection to the environment, object of protection and juridical tutelage, because it is the condition ofthe own existence and the realization of the other human rights. Finally, it is argued that the protection of the ecological existential minimum for all individuals would be in conformity with the premises of a socio - environmental State and, in the final analysis, that it is one of the forms of realization of a theory of justice.